2004
DOI: 10.1158/0008-5472.can-03-2592
|View full text |Cite
|
Sign up to set email alerts
|

RTVP-1, a Tumor Suppressor Inactivated by Methylation in Prostate Cancer

Abstract: We previously identified and characterized a novel p53-regulated gene in mouse prostate cancer cells that was homologous to a human gene that had been identified in brain cancers and termed RTVP-1 or GLIPR. In this report, we document that the human RTVP-1 gene is also regulated by p53 and induces apoptosis in human prostate cancer cell lines. We show that the expression of the human RTVP-1 gene is down-regulated in human prostate cancer specimens compared with normal human prostate tissue at the mRNA and prot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
71
1
2

Year Published

2006
2006
2013
2013

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 60 publications
(79 citation statements)
references
References 21 publications
(27 reference statements)
5
71
1
2
Order By: Relevance
“…Unfortunately, there are only limited data available on the biological role of GLIPR1, but this report suggests it may play an important role in prostate cancer progression. To date, this is the only report of methylation of GLIPR1 in cancer (Ren et al 2004).…”
Section: Glipr1mentioning
confidence: 89%
See 1 more Smart Citation
“…Unfortunately, there are only limited data available on the biological role of GLIPR1, but this report suggests it may play an important role in prostate cancer progression. To date, this is the only report of methylation of GLIPR1 in cancer (Ren et al 2004).…”
Section: Glipr1mentioning
confidence: 89%
“…GLIPR1 has T M Murphy et al: DNA methylation, aberrant cell death and prostate cancer www.endocrinology-journals.org been shown to be down-regulated in prostate cancer compared with normal prostatic tissue (Ren et al 2004). DNA methylation appeared to be a prevalent method of down-regulation and GLIPR1 gene expression could be restored by treatment with a demethylating agent.…”
Section: Glipr1mentioning
confidence: 99%
“…Because RTVP-1 is induced during the differentiation of specific antigen-presenting cells, 16 we favor the notion that intrinsic immunostimulatory properties of RTVP-1 are more related to the activation of downstream, potentially receptor-mediated, signaling cascades within antigenpresenting cells rather than intrinsic antigenic properties. As we have shown that the expression of RTVP-1 is significantly reduced in advanced cancers, 17 the therapeutic use of RTVP-1 is less appealing as a tumor antigen than as an immunomodulator.…”
Section: Discussionmentioning
confidence: 99%
“…13 Recently, we have extended these studies to show that the human RTVP-1 gene is also regulated by p53, functions as a tumor suppressor and is inactivated by gene methylation in prostate cancer. 17 In a preclinical gene therapy model, we demonstrated that adenoviral vectormediated RTVP-1 expression can suppress growth and metastasis of prostate cancer in vivo, 18 and that these effects are mediated by proapoptotic, antiangiogenic and immunostimulatory activities. In the present study, we tested the ability of RTVP-1 to enhance the therapeutic potential of whole tumor cell vaccination in a metastatic prostate cancer model designed to mimic the effects of recurrent prostate cancer in humans.…”
Section: Introductionmentioning
confidence: 94%
“…The relative expression of each mRNA was determined by using threshold cycle comparisons to the standard curve method described by the manufacturer and normalized to 18S RNA as described. 50 In vivo studies After trypsinization, 178-2 BMA cells were resuspended in Hanks' balanced salt solution (HBSS) at 5 Â 10 4 cells in 50 ml. Tumors were established in 4-6-month-old syngeneic 129/Sv mice by subcutaneous injection.…”
Section: Il-12 Gene Therapy and Radiotherapy T Fujita Et Almentioning
confidence: 99%